KUALITAS PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN DI KLINIK TERPADU POLTEKKES KEMENKES TANJUNGKARANG - Sunarsih Sunarsih; Yuniastini Yuniastini (Jurnal Kesehatan, 2014)
Sunarsih1)Yuniastini) 1)Jurusan Keperawatan Poltekkes Kemenkes Tanjungkarang Abstrach :Health service quality with patient’s satisfaction levels, in integrated clinic Health Polytechnics of health ministry Tanjungkarang.Integrated clinic is a Health Polytechnics unit of Health Ministry Tanjungkarang that has functions as a supporting element of the learning process for students and also a place for research by college lecturer , to support these functions, these clinics provide health services for students and also for general public. Data from 2010 until 2012 stated that the number of clinic’s visitorswas increased, but the increase was relatively small. while the results of the research from Saputri Reni (2009) about community’s perceptions of health services in integrated clinic , said mostly public perception were in the quite good categories. This research aims to analyze the relationship between the quality of health services with the level of patient’s satisfaction. The type of this research is explanative survey. The samples in this research amounted to 63 people that were taken using accidental sampling technique.The result showed that patients who utilize services in integrated clinic Health Polytechnics of health ministry Tanjungkarang is mostly students. The highest patient’s satisfaction is an explanation of the actions to be performed after the patient in a residence or home. while the lowest patient’s satisfacton is the speed of the clinicians in giving treatment to the patient. The result of Spearman's rho test obtained there is a very strong and positive relationship between the quality of health services and the level of client satisfaction in the integrated clinic Health Polytechnics of health ministry Tanjungkarang (p : 0,000 ; a = 0,05 ; r = 0,850). Keywords: client satisfaction, clinic health Abstrak:Kualitas  Pelayanan  Kesehatan dengan Tingkat Kepuasan Pasien di Klinik Terpadu Poltekkes Kemenkes Tanjungkarang. KlinikTerpadumerupakan  unit di Poltekes Kemkes Tanjungkarang, yang berfungsi sebagai unsur penunjang proses pembelajaran bagi mahasiswadantempatpenelitianbagidosen. Untuk menunjang fungsi tersebut,  klinik ini memberikan pelayanan jasa kesehatan kepada mahasiswa dan umum. Data tahun 2010 sampai 2012 angka kunjungan keklinikmeningkat, namun peningkatan tersebut relatif sedikit.Sementara hasil penelitian Saputri Reni (2009) tentang Persepsi Masyarakat terhadap Pelayanan Kesehatan di Klinik Terpadu sebagian besar  persepsi masyarakat dalam kategoricukup (52,5%). Penelitian ini bertujuan untuk menganalisis hubungan kualitas pelayanan kesehatan dengan tingkat kepuasan pasien. Jenis  penelitian adalah explanative survey. Sampel penelitian sebanyak 63 orang diambil dengan teknik accidental sampling. Hasil penelitian didapatkan, pasien yang memanfaatkan pelayanan di Klinik Terpadu Poltekes Kemenkes Tanjungkarang sebagian besar adalah mahasiswa. Kepuasan pasien yang tertinggi adalah ‘penjelasan tindakan yang harus dilakukan  pasien setelah di tempat tinggal/ rumah’. Sementara kepuasan terendah adalah ‘kecepatan petugas dalam memberikan pertolongan kepada pasien’. Hasil uji Spearman's rho didapat  ada hubungan yang sangat kuat dan positif antara kualitas pelayanan kesehatan dengan tingkat kepuasan pasien di Klinik Terpadu Poltekes Kemenkes Tanjungkarang (p = 0,000 ; α =0,05 ;  r = 0,850 ). Kata Kunci :  Kualitas, Kepuasan, Pasien